Metabolic activities and ultrastructure imaging at late-stage of wood decomposition in interactive brown rot - white rot fungal combinations - Mali, Tuulia; Laine, Karoliina; Hamberg, Leena; Lundell, Taina (Elsevier BV, 2023)
Basidiomycota brown rot fungus (Fomitopsis pinicola) and two white rot fungi (Phlebia radiata, Trichaptum abietinum) were cultivated on thin slices of spruce wood individually and in interspecies combinations. Within 12 months, F. pinicola substantially decomposed spruce wood observed as mass loss, also in three-species combinations. However, white rot fungi through hyphal interactions negatively affected the brown-rot indicative iron reduction capacity of F. pinicola. Decay-signature gene expression in mycelial interaction zones indicated suppression of brown rot mechanism but stimulation of enzymatic white-rot lignin attack by P. radiata. Wood ultrastructure imaging showed white-rot dominance in the fungal combinations, whereas destructive brown-rot was evident with F. pinicola alone. Our results confirm the dynamic pattern of enzyme production in fungal combinations, and transition from brown to white rot decomposition metabolism during the late stage of wood decay after one year of interspecific interactions.
Keywords: Basidiomycota; Interspecific interactions; Iron reduction; Oxalic acid; Enzyme activity; Laccase; Manganese peroxidase; Wood biodegradation; White rot; Brown rot